Effect of Rosuvastatin on Myocardial Apoptosis in HypertensiveRats Through SIRT1/NF-κB Signaling Pathway: Effect of Rosuvastatin on Myocardial Apoptosis - Ren, Xiangqian; Wang, Yi; Han, Lin; Sun, Zhenzhen; Yuan, Bin (Cellular and Molecular Biology, 2022)
The study aimed to observe the effect of rosuvastatin on myocardial apoptosis in hypertensive rats through the silent information regulator 1 (SIRT1)/nuclear factor-κB (NF-κB) signaling pathway. The spontaneously hypertensive rat (SHR) model was established, and the rats were randomly divided into the SHR group, Rosuvastatin group and Control group. The blood pressure, creatine kinase (CK) and other myocardial indexes in each group were detected, the cardiac function indexes of rats were determined using magnetic resonance imaging (MRI) and echocardiography (ECG), and tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in myocardial tissues were detected via enzyme-linked immunosorbent assay (ELISA). Moreover, the apoptosis level of myocardial tissues was detected using terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. Finally, the expression levels of the SIRT1/NF-κB signaling pathway and apoptosis genes and proteins in myocardial tissues in each group were detected via quantitative polymerase chain reaction (qPCR) and Western blotting. In the SHR group, the blood pressure, the levels of serum creatinine (CR) and CK were increased (p<0.05). In the SHR group, both fractional shortening (FS%) and ejection fraction (EF%) were obviously lower than those in the control group (p<0.05), while both left ventricular end-diastolic diameter (LVEDd) and left ventricular end-systolic diameter (LVESd) were higher than those in the control group (p<0.05), and the levels of TNF-α, IL-6 and myeloperoxidase (MPO) were increased (p<0.05). The number of apoptotic cells in myocardial tissues in the SHR group was larger than that in the other two groups (p<0.05). In the SHR group, the expression levels of Caspase3 and NF-κB were remarkably higher than those in the Rosuvastatin group (p<0.05), while the expression levels of Bcl-2 and SIRT1 were remarkably lower than those in the Rosuvastatin group (p<0.05). Rosuvastatin can inhibit myocardial apoptosis in hypertensive rats through up-regulating SIRT1 and down-regulating NF-κB.